Compulsory English Online Learning Practices in Kapuas Hulu Regency - Olivia Ellasari Bua’a; Dedi Irwan; Sahrawi Sahrawi (XXXX-XXXX, 2021)
This study aims to evaluate online learning practices carried out by schools during the COVID-19 pandemic in Kapuas Hulu Regency. The results of this study are expected to provide an overview of the implementation of online learning that can be carried out in the future so that it can run properly. This research was conducted using a descriptive qualitative approach involving 4 schools spread across Kapuas Hulu Regency, namely with two school contexts located in rural and urban areas. In this study, four secondary schools were involved which included two different sub-districts, namely Bika District and South Putussibau District. The data analysis used in this research is descriptive qualitative, using thematic analysis and cross-case analysis techniques. The results of this study are in the form of recommendations for improving the application of online learning models in the future by considering the results of the evaluation of online learning practices that have been implemented in implementing online learning.Keywords: Online Learning Practice, School Improvement, English Learning